Strategi Penetapan Harga : Studi Kasus pada Kebab Ajo Lubeg (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Pricing is a critical factor determining the success of small and medium-sized enterprises (SMEs) in the market. This study investigates the pricing strategy implemented by Kebab Ajo Lubeg, a culinary SME located near Universitas Putra Indonesia YPTK Padang. The research aims to analyze how pricing methods are applied, the factors considered in price determination, and their influence on consumer purchasing decisions and business strategy. A qualitative descriptive approach was employed, with data collected through semi-structured interviews with the owner and employees, direct observation, and documentation of product offerings and pricing. Findings indicate that Kebab Ajo applies a combination of cost-based pricing, competition-based pricing, and product-based price variation to balance production costs, consumer purchasing power, and market competition. The pricing strategy significantly affects consumer satisfaction, repeat purchases, perceived value, brand image, and business competitiveness. This study provides practical insights for other SMEs in setting appropriate prices while maintaining customer loyalty and profitability, and it contributes to the academic discourse on marketing management and pricing strategies in the culinary sector.